Student Engagement Using Field Work and Cross Cultural Immersion - Marchioro, Gary (INTI University College, 2009)
This paper discusses the process and educational value of student offshore field trips within a unit of tertiary study. The paper outlines the structure for a Business in Asia unit of study which combines local students (Australian) and students visiting from a partner university in the US and unites both cohorts to an Asian destination for an Intensive business and cultural field trip. The experiential learning, cultural mix and the development of a sense of understanding of diversity within a cultural context arc presented. The learning process In terms of negotiating and experiencing other cultural environments is also examined. In addition, the overall mix of working on an international business assignment with different nationalities was a further challenge to the Learning process and one that is now commonplace in the modern global educational system.